Family law services handbook : the role of the financial expert - Glenn, Donald A. (John Wiley, 2011)
Up to fifty percent of financial forensic services are performed in divorces, or in family law business valuations. Providing the first definitive publication on family law for accountants, this book addresses topics unique to family law accounting, tax, valuation and practice